IMPLEMENTATION OF FULL DAY SCHOOL AS FORMATION OF STUDENT CHARACTER AT SMA NEGERI 2 BULUKUMBA: Implementasi Full Day School sebagai Pembentukan Karakter Siswa di SMA Negeri 2 Bulukumba - Prayoga Saputra Yoga; Pattaufi; Merrisa Monoarfa (STKIP Subang, 2024)
The problem of this research is how a full day school program can shape the character of students at SMA Negeri 2 Bulukumba. The aim of this research is to determine the implementation of full day school as a form of character for students at SMA Negeri 2 Bulukumba. This research approach uses a qualitative approach with descriptive research type. The data sources for this research are the principal, deputy principal for curriculum, deputy principal for student affairs, teachers and students, as well as the students' parents. Data collection techniques were carried out using interviews, observation and documentation. Data analysis techniques use data reduction analysis, data display and data verification. Triangulation is to explain the validity of data using various sources. The research results show that implementing full day school is a form of student character formation. Implementation of full day school includes an innovative learning system that covers cognitive, affective and psychomotor domains; Implementation of a tutoring system to fulfill character education values ​​which include curiosity, hard work and communicativeness; Extracurricular lessons which include scouts, PMR, paskib, sports and arts; The integration of character values ​​in subjects which include the 18 character education values ​​of the Ministry of National Education, and the school culture program is carried out as an habit for all school members which includes Al-Qur'an literacy, collective Dhikr, obligatory prayers, Friday alms and discipline. With the school culture program, parents feel the changes their children experience, such as their children's attitudes becoming more devout in religious matters and more fluent in reading the Al-Qur'an, thereby forming students' character in the religious aspect. It can be concluded that the implementation of full day school can shape the character of students which includes the Ministry of National Education's character education values ​​in various ways and activities at school.